Postoperative Nausea and Vomiting Following Craniotomy: Risk Factors and Complications in Context of Perioperative High-dose Dexamethasone Application - Burkhardt, Till; Czorlich, Patrick; Mende, Klaus Christian; Treitz, Annika; Kiefmann, Rainer; Westphal, Manfred; Schmidt, Nils Ole (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Introduction Postoperative nausea and vomiting (PONV) is common in patients after craniotomy and may lead to severe postoperative complications. The aim of this study was to identify risk factors and postoperative complications associated with PONV in the context of perioperative high-dose dexamethasone administration.Patients and Methods In this prospective single-center study, all patients planned for elective craniotomy for supra- and infratentorial lesions were eligible to be included. Any PONV in a 24-hour period after craniotomy was recorded and analyzed with regard to time to postoperative complications and the administration of perioperatively administered high-dose dexamethasone.Results The overall PONV rate of 421 patients during a 9-month period was 18.1% (76 patients). Multivariate analysis revealed a significant association of PONV with female sex, infratentorial localization, age, and history of PONV. There was no association between PONV and postoperative complications such as intracranial hemorrhage, cerebrospinal fluid (CSF) leaks, or pneumonia. Perioperative administration of high-dose dexamethasone for prophylactic prevention of edema was the only significant risk factor for postoperative complications (odds ratio [OR]: 3.34; confidence interval [CI], 1.39–8.05; p < 0.01) with a highly significant association with the occurrence of CSF leaks (OR: 6.85; CI, 1.62–29.05; p < 0.01).Conclusion The low PONV rate of 18.1% in this study may be the result of the frequent perioperative administration of high-dose dexamethasone for the prevention of edema. Our data indicate that perioperative high-dose dexamethasone is significantly associated with CSF leaks and can therefore not be recommended on a regular basis.
Keywords: PONV; craniotomy; complications; dexamethasone; CSF leaks